The Pancasila Fortress Campus Tourism Model in Character Strengthening at Sebelas Maret University of Surakarta - Bramastia Bramastia; Leo Agung Sutimin; Djono Djono; Winarno Winarno; Andrea Salsalova (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This research aims to develop the Pancasila Fortress Campus Tourism Model at Sebelas Maret University (UNS) Surakarta as a character-learning strategy grounded in Pancasila values. The research approach uses mixed methods with descriptive qualitative dominance. Data were obtained through questionnaires, interviews, observations, and documentation involving 148 students of SMA Persatuan Kedungpring Lamongan and 12 mentors, with 100 students as questionnaire respondents. Qualitative data analysis used Miles and Huberman's interactive model, and the instrument's reliability was assessed using Cronbach's Alpha, yielding a value of 0.891, indicating high internal consistency. The study's results show that Pancasila Fort Campus Tourism activities significantly strengthen participants' character, particularly in tolerance, nationalism, and cultural appreciation. The developed model consists of five main components: understanding of the learning model, activity design, implementation, evaluation, and general assessment. Participants responded positively, with an average score in the good-to-very good range, and 90% stated that this program is feasible to implement continuously. This finding confirms that campus tourism is not only a means of introducing the university environment but also an effective experiential learning medium for internalizing Pancasila values in context. This model has the potential to be replicated across various educational institutions as a best practice for strengthening character education.